(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2022)
In 2020, the COVID-19 pandemic has had a huge impact on the education system in Malaysia, especially at higher education level. A number of public or private universities have carried out online learning classes due to the Covid-19 pandemic and avoid the spread of the virus among university students. Face to-face learning can not be implemented because the learning efficiency in class management decreased. Thus, this study discussed the integration of wireless sensors within the classroom, focusing on improvement of ventilation system and learning efficiency in classroom design. As a result, the goals of this research are to identify the types of wireless sensors that can be used to improve the ventilation system in classroom design, to identify the mechanisms of wireless sensors that can be used to improve the ventilation system in classroom design, and to propose design guidelines for using wireless sensors to improve the ventilation system and learning efficiency in classroom design. Reviews on related topics such as wireless sensor technology and smart classroom will be made via online searching articles and journals. Acquisition of primary data and secondary data will be done via case study of smart classroom from relevant articles and journals.